Time trends of myocardial infarction 28-day case-fatality in the 1990s: is there a contribution from different changes among socioeconomic classes?. Issue 7 (16th June 2008) - Fornari, C; Cesana, G C; Chambless, L E; Corrao, G; Borchini, R; Madotto, F; Ferrario, M M; ,
Abstract : Background/objective: Almost two-thirds of the coronary death rate decrease in the northern Italian Brianza MONICA male population, between 1993–4 and 1997–8, are attributable to a reduction in 28-day myocardial infarction (MI) case-fatality. The present paper investigates the factors associated with MI case-fatality decrease and in particular the role of socio-occupational classes (SOCs). Methods: Standardised information on acute coronary care and intervention before and during the hospitalisation was collected for all coronary events (n = 1817) registered in 1993–4 and in 1997–8 among 35–64-year-old male residents in Brianza. Deaths within 28 days after MI were carefully investigated. Five SOCs were defined adopting the Erikson-Goldthorpe-Portocarero method. Differences in 28-day MI case-fatality and in acute phase intervention and treatment over time and among SOCs in each period were assessed. Results: 28-day MI case-fatality reduction (27.2%) can be mainly attributed to a decreased proportion of MI events that were fatal before reaching the hospital. In the lower SOCs significant changes in MI case-fatality were detected between 1993–4 and 1997–8. Differences in acute phase intervention and treatment between the periods were observed. SOC differences both in prevalence of out-of-hospital cardiac arrest and in the pre-hospital qualified intervention score were detected in the first period only. Conclusions: In the study population MI case-fatality reduction can be mainly attributed to a more effective and prompt management before hospitalisation and to an improvement in acute treatment during hospitalisation. This enhancement is made available to the whole population overtaking social differences.